Pengaruh PAD, DBH, DAU, dan SiLPA Terhadap Belanja Bantuan Sosial Pada Pemerintah Daerah Se-Bakorwil Madiun - Nurharibnu Wibisono; Herry Purnomo; Endang Edy Rahaju (Universitas Merdeka Madiun, 2021)
Abstractâ€” This study aims to examine the effect of the Regional Original Revenue (PAD), the Revenue Sharing Funds (DBH), the General Allocation Fund (DAU), and the Remaining Budget Calculation (SiLPA) on Social Assistance Expenditure (Bansos) in Local Governments as the Madiun Regional Coordination (Bakorwil) both partially and simultaneously. The research objects were 10 (ten) Regional Governments in Bakorwil Madiun, East Java, Indonesia based on the realization of APBD data for the period 2011 - 2018. Multiple linear regression method with the help of SPSS 20 was used as an analytical tool in this study. The results of this study indicate PAD, DBH, and DAU affect the Social Assistance Expenditure in Local Governments as the Madiun Regional Coordination (Bakorwil). Whereas SiLPA has no effect on Local Governments as the Madiun Regional Coordination). Simultaneously shows PAD, DBH, DAU, and SiLPA influences the Social Assistance Expenditure in Local Governments as the Madiun Regional Coordination.Â Keywordsâ€”: Regional Original Revenue; Revenue Sharing Fund; General Allocation Fund; Remaining Budget Calculation; and Social Assistance Expenditure.